Peningkatan Kualitas Air Sungai Deli Dengan Menggunakan Kijing (Pilsbryoconcha exilis) Sebagai Biofilter Bakteri Patogen (Escherichia coli) - Fici My Safitri Tanjung; E. Harso Kardhinata; Abdul Karim (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2022)
Water  is  a  basic  need  for  humans  because  it  is  needed,  among  others,  for  households,  industry, agriculture and improving public health. Clean water that meets the standards, namely physical, chemical, and microbiological requirements. Escherichia coli is one of the microbiological indicators in water. One of the sources of clean water used by the people in the city of Medan comes from the Deli river. The development of industry and settlements around the Deli river causes water pollution. Freshwater mussel as a biofilter that can be used to maintain the water quality of the Deli river. This study aims to determine the effective use of mussel as a biofilter of Escherichia coli bacteria and the most effective length of time to improve water quality. This study used RAL (Completely Randomized Design) with treatment durations K0 (Control), K1 (Day 5), K2 (Day 10 days) and Day 15. The results showed that mussel was effectively used as a biofilter to reduce the number of Escherichia coli and for 10 days was quite effective in reducing the number of Escherichia coli in Deli river water.